Foliar Application of Indole-3-Butyric Acid and Gibberellic Acid Alters Growth and Yield of Carrot (Daucus Carota L.) Cv. “Shidur” - Afroze, Farjana; Akter, Ayasha; Hossain, Md. Mokter (Department of Agronomy and Horticulture, IPB University, 2025)
Carrots are a nutritious and well-accepted root crop in Bangladesh, but production is very low at the farmer's field level compared to the other producing countries. Therefore, this study was undertaken to improve the yield of carrots by using different plant growth regulators. To evaluate the influence of the foliar application of indole-3-butyric acid (IBA) and gibberellic acid (GA3) on the growth and yield of carrots, different concentrations viz., 0, 50, 100, 150 ppm of IBA and GA3 were sprayed at the vegetative stage of carrot production. Among all the treatments, 150 ppm GA3 shows better shoot growth with the highest plant height (56.80 cm), number of leaves (10.53), leaf length (56.81 cm), fresh weight of leaves (57.08 g), and dry matter content of leaves (10.95%). Foliar application of 150 ppm IBA significantly increased root traits, including root length (16.20 cm), diameter (3.92 cm), fresh weight per plant (98.45 g), and dry matter content (12.01%). Moreover, gross yield (36.80 tons per ha) and marketable yield (36.21 tons per ha) were the highest when IBA was applied at 150 ppm. Overall results revealed that 150 ppm IBA resulted in better growth and higher yield in carrot cv. “Shidur” compared to other treatments.